Cyber Crime and Its Entext (Global Journal of Computer Science and Technology, 2023)
Any crime that uses a computer or network is considered a cybercrime sometimes known as computer crime People and businesses are exposed to the expanding hazards of cybercrime as a result of their increased reliance on technology Nowadays it s pretty typical for us to use computers for our daily tasks
Keywords: cybercrime; cyberlaw; cybercrimes in india; it act 2000; effects caused by cybercrime; cyber security; extent of the crime